Four-week trunk-specific exercise program decreases forward trunk flexion in Parkinson's disease: A single-blinded, randomized controlled trial. (July 2019) - Gandolfi, Marialuisa; Tinazzi, Michele; Magrinelli, Francesca; Busselli, Giulia; Dimitrova, Eleonora; Polo, Niccolò; Manganotti, Paolo; Fasano, Alfonso; Smania, Nicola; Geroin, Christian
Abstract: Introduction: Pathological forward trunk flexion is a disabling and drug-refractory motor complication of Parkinson's disease (PD) leading to imbalance, pain, and fall-related injuries. Since it might be reversible, early and multidisciplinary management is emphasised. The primary aim was to compare the effects of a four-week trunk-specific rehabilitation program on the severity of the forward trunk flexion. The secondary aim was to compare the training effects on the motor impairments, dynamic and static balance, pain, falls, and quality of life. Methods: 37 patients with PD (H&Y ≤ 4) and forward trunk flexion were randomized in the experimental (n = 19) or control group (n = 18). The former consisted of active self-correction exercises with visual and proprioceptive feedback, passive and active trunk stabilization exercises and functional tasks. The latter consisted of joint mobilization, muscle strengthening and stretching, gait and balance exercises. Protocols lasted 4 weeks (60 min/day, 5 days/week). Before, after, and at 1-month follow-up, a blinded examiner evaluated patients using primary and secondary outcomes. The primary outcome was the forward trunk flexion severity (degree). Secondary outcomes were the UPDRS III, dynamic and static balance, pain falls, and quality of life assessment. Results: The experimental group reported a significantly greater reduction in forward trunk flexion than the control group from T0 to both T1 (p = 0.003) and T2 (p = 0.004). The improvements in dynamic and static balance were significantly greater for the experimental group than the control group from T0 to T2 (p = 0.017 and 0.004, respectively). Comparable effects were reported on the other outcomes. Pre-treatment forward trunk flexion values were highly correlated to post-treatment trunk deviation changes. Conclusion: The four-week trunk-specific rehabilitation training decreased the forward trunk flexion severity and increased postural control in patients with PD. NCT03741959. Highlights: Forward trunk flexion is a disabling and drug-refractory motor complication. Promoting an early and multidisciplinary management is essential. Specific trunk rehabilitation decreases forward trunk flexion posture.